Determination of Kinetic Parameters for the Oxygen Reduction Reaction on Platinum in an AEMFC. Issue 12 (2nd December 2021) - Grimler, Henrik; Carlson, Annika; Ekström, Henrik; Lagergren, Carina; Lindström, Rakel Wreland; Lindbergh, Göran
Abstract : To promote the development of anion exchange membrane fuel cells (AEMFC), an understanding of the oxygen reduction reaction (ORR) kinetics in porous gas diffusion electrodes is essential. In this work, experimental polarisation curves for electrodes with different platinum catalyst loadings and oxygen partial pressures at the cathode are fitted to a physics-based porous electrode model in the voltage range from open circuit voltage (OCV) to 0.7 V. Polarisation curves measured with different anode catalyst loadings, and hydrogen partial pressures, were used to verify the model. The reactions are described using a two-step Tafel-Volmer pathway at the anode and concentration-dependent Butler-Volmer kinetics at the cathode. A good fit to experimental data in the kinetic region is obtained with an exchange current density of 1.0 · 10 − 8 A cm − 2, a first order dependency on oxygen partial pressure, and a charge transfer coefficient of 0.8 for the ORR. For lower oxygen partial pressure, hydrogen crossover is needed to explain the downward shift of the polarisation curves in the kinetic region. In the experimental data, the polarisation curves show an apparent limiting current density at lower hydrogen partial pressures, explained by the lower rate of the Tafel step at these conditions.